Synthesis, characterization and molecular structure of the complex [ Re2(CO)6(C14H11N4)(OH) ]2. - Goite, María Cristina; Machado, Rubén; Rivillo, David; De Sanctis, Ysaura; Arce, Alejandro; Deeming, Antony; Atencio, Reinaldo; Briceño, Alexander; D”™Ornelas, Lindora (Ciencia, 1970)
Ver resumen pdf.